PENGARUH PEMAHAMAN, KESADARAN, SIKAP RASIONAL, PERUBAHAN TARIF, TINGKAT PENDIDIKAN DAN SOSIALISASI TERHADAP KEPATUHAN PELAKU UMKM DI PEKANBARU DALAM MELAKSANAKAN KEWAJIBAN PERPAJAKAN (Peraturan Pemerintah Nomor 46 Tahun 2013) - Anggrainy Eka Putri Marpaung; Zulbahridar '; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The objective of this research was to analyze the influence of comprehension, awareness, rationality, tarif change, level of education, and socialiszation to compliance of Comprehension of Micro, Small, and Medium Enterprises in doing his tax obligation (Government Regulation No. 46 Year 2013). The population in this research is Comprehension of Micro, Small and Medium Enterprises that registered in the cooperation official and Micro, Small, and Medium Enterprises Pekanbaru. Data collected through questionnaires are processed and analyzed by using multiple regression analysis method. Sample was determined by Slovin that result 97 samples. The test for data quality are using validity of test to use is pearson correlation and reliability test of the research to use is cronbach alpha. For hypotesis test, we are using Adjusted R square, F test and t test. The test results of this study indicate that comprehension, awareness, tarif change, and socialiszation effect on compliance of Comprehension of Micro, Small and Medium Enterprises in doing his tax obligation (Government Regulation No. 46 Year 2013). Meanwhile rationality have negative effect and level of education have no effect on compliance of Comprehension of Micro, Small and Medium Enterprises in doing his tax obligation (Government Regulation No. 46 Year 2013).Keywords : comprehension, awareness, rationality, tarif, and socialiszation.